Pengaruh Program Praktik Kerja Terhadap Pilihan Jenjang Karir Program Keahlian Teknik Otomotif SMK N 2 Surakarta - Muhammad Rosyiq Aiman; Ngatou Rohman (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2025)
Career planning is a critical component for Vocational High School (Sekolah Menengah Kejuruan or SMK) students to ensure their readiness to enter the professional world. As the job market becomes increasingly competitive, students need to be equipped not only with technical knowledge but also with the ability to align their interests, talents, and capabilities with the demands of the industry. Research has shown that students with well structured career plans demonstrate greater confidence, clarity, and competence in making career-related decisions. This study aims to examine the influence of the Industrial Work Practice program on the career development of students enrolled in the Automotive Engineering program at SMK N 2 Surakarta. The program provides students with firsthand industry experience, allowing them to acquire practical skills, improve problem-solving abilities, and enhance their motivation to pursue relevant career paths. To ensure the validity of the research findings, a series of instrument testing procedures were applied, including tests for validity, reliability, normality, linearity, and heteroscedasticity. These steps were crucial in confirming that the data accurately represented the variables under study. Hypothesis testing was carried out using both F-tests and t-tests to determine the individual and collective effects of the Field Work Practice program on students' career choices. The results showed a statistically significant impact of the program on students’ career readiness, particularly in terms of their engagement in the program, the competencies they developed during the practice, and their career motivation.